The Misguided Assault on the Consumer Welfare Standard in the Age of Platform Markets - Melamed, A. Douglas; Petit, Nicolas (Review of industrial organization, 2019)
In this paper, we discuss whether the consumer welfare (CW) standard needs to be replaced or revised in order for antitrust law to deal effectively with the economic challenges of the platform economy. We argue that both the general and platformspecific assaults on the CW standard are misguided, that the CW standard is capable of addressing the economic concerns that critics have raised, and that the proposed alternatives would make things worse—not better.